HISTOPATOLOGI KARDIOVASKULAR PADA PASIEN DENGAN INFEKSI COVID-19 TINJAUAN SYSTEMATIC REVIEW - Rizkia Ulhaq (2021)
Coronavirus disease 2019 (COVID-19) is a disease caused by the SARS-CoV-2 virus. This disease can attack multiple organs including the cardiovascular system which can increase the risk of patient mortality. Cardiovascular histopathological features are the second most common after histopathological features in the respiratory system. However, research related to this is still very limited. The purpose of this discussion is to determine the cardiovascular histopathology in patients with COVID-19 infection. Method: Systematic Literature Review by conducting a literature search using PubMed. The forms of literature taken are case reports, case series and cohort studies. The literature must contain COVID-19 patients who were autopsied or performed post-mortem biopsies of the heart and then seen the histopathological picture under a microscope. Results: There were 32 journals with 22 of them using a Case Series research methodology, 8 journals using a Case Report research methodology and 2 journals using a Cohort Study research methodology. All journals describe the histopathological features of the heart. Conclusion: Histopathological abnormalities found in the heart were inflammatory infiltrate of the myocardium without necrosis, myocardial injury or acute myocyte necrosis, myocarditis, pericarditis, myocardial edema and acute myocardial infarction. Histopathological abnormalities found in the coronary arteries are thrombus/ microthrom